Climate policies with pollution externalities and learning spillovers - Paul Lehmann (Helmholtz-Zentrum für Umweltforschung (UFZ), 2009)
Economic theory suggests that with a pollution externality and learning spillovers related to renewable energy technologies, the optimal climate policy mix includes an emissions policy and an output subsidy to the learning industry. Instead of output subsidies, feed-in tariffs are often implemented in addition to emissions policies. This paper reveals that this policy mix may theoretically provide for a first-best outcome as well. However, its efficient design may be cumbersome for regulators. An emissions tax must be below the Pigovian level and differentiate between fossil fuels. Moreover, both tax and feed-in tariff must be adapted continuously.
Keywords: D62; Q48; Q54; Q58; 360; Emissions tax; feed-in tariffs; policy mix; spillovers; learning by doing; Klimaschutz; Ökosteuer; Internalisierung externer Effekte; Förderung regenerativer Energien; Stromtarif; Administrierter Preis; Policy-Mix; Lernprozess; Spillover-Effekt; Theorie